Analysis of low-angle X-ray scattering profiles from irradiated blood samples. (19th November 2009) - Pinto, N.G.V.; Cardoso, E.R.; Almeida, A.P.G.; Braz, D., R.T. Lopes, R.C. Barroso
The Transfusion-Associated Graft-Versus-Host Disease (TA-GVHD) is a serious potential complication of blood transfusions that is essentially prevented by blood product irradiation. In this study, scattering profiles from lyophilised and irradiated samples of plasma (PL) and formed elements (MC) were compared with non-irradiated ones. Fresh blood specimens were obtained from volunteers by vein puncture using vacutainer tubes containing ethylenediaminetetraacetic acid (EDTA). All the samples were lyophilised for 48 h in a freeze drier. The scattering measurements were carried out using a powder diffractometer. The measured characterisation parameters for Low-Angle X-ray Scattering (LAXS) were associated with epidemiological data (age). The mean values of the different parameters were compared using the Student's t-test for each characterisation parameter. The scattering profiles from PL and MC are characterised by the presence of two peaks in the forward direction of scattering.